# The author uses the word "immediacy" (line 39) most likely in order to express

Kathryn on January 1, 2019

Missing Premise

Hello, I am having huge issues with the missing premise drills. I understand the example you show in the discussions previously, but I am having an issue applying it to other scenarios. For example, I can get the simple P: P: and C: ones but once theres a third premise added I get confused and somehow end up with the contrapositive of the missing premise instead of the positive. How do you know which one is right? Thank you.

Replies

Kathryn on January 1, 2019

To further specify on the flashcard
P: not X-->not Y

P:

C: not X-->not B

P:not X--> not Y
Y-->X
P:

C:not X-->not B
B-->X

so, not x-->not Y -->not B
so not Y--> not B would be the missing premise with
B--> Y as the contrapositive, but the answer has it the other way around.

This is specifically where I am confused. Thanks.

Ravi on January 1, 2019

@kzieno,

Happy to help! It sounds to me like you're either 1) confusing the
necessary for sufficient conditions when diagramming or 2) you've
actually correctly diagrammed the sufficient and necessary conditions
but have simply done so in a way that gives you the contrapositive. Do
you have a concrete example from one of the specific questions you're
having difficulty with? That would help me better see exactly what
you're doing in the context of the problem.

The great thing about contrapositives is that they're logically
equivalent to the original sufficient and necessary condition.

Let's say that you've diagrammed a premise as not B - ->not A, and the
original premise was A - ->B. All you need to do is flip the signs and
the position of not B - ->not A (making it A - ->B), and you have the
original sufficient and necessary conditions and a logically
equivalent statement.

In statements with three or more premises, it helps to pay close
attention to figure out how each of the premises is used to support
the overall conclusion of the argument. Sometimes, you'll find that
one or more of these premises is a subsidiary conclusion, which is a
something that is supported by premises but is also used to support
another statement in the argument.

Does this make sense? If you could send over an example of a specific
problem that you're having difficulty with, that would be very helpful
so that we could through it together. Let us know if you have any more
questions!

Ravi on January 1, 2019

@kzieno,

Apologies; just after I posted my original response, you uploaded the
specific problem you were having a problem with. Let's take a look at
it.

Your analysis looks great. In the flash card problem you presented,
you're correct: not Y - ->not B would be the missing premise, with
B - >Y as the contrapositive. What does the answer say? not Y - ->not B?
If the answer says not Y - ->not B, then that's fine, as the LSAT often
puts the answer in the contrapositive to test whether or not you know
that the original statement and the contrapositive are logically
equivalent to one another.

Does that make sense? If there are more details to the problem, please
let us know!